Orientation-aware plasma cell-free DNA fragmentation analysis in open chromatin regions informs tissue of origin - Sun, Kun; Jiang, Peiyong; Cheng, Suk Hang; Cheng, Timothy H.T.; Wong, John; Wong, Vincent W.S.; Ng, Simon S.M.; Ma, Brigette B.Y.; Leung, Tak Y.; Chan, Stephen L.; Mok, Tony S.K.; Lai, Paul B.S.; et al. (Genome Research, 2019)
Cell-free DNA (cfDNA) in human plasma is a class of biomarkers with many current and potential future diagnostic applications. Recent studies have shown that cfDNA molecules are not randomly fragmented and possess information related to their tissues of origin. Pathologies causing death of cells from particular tissues result in perturbations in the relative distribution of DNA from the affected tissues. Such tissue-of-origin analysis is particularly useful in the development of liquid biopsies for cancer. It is therefore of value to accurately determine the relative contributions of the tissues to the plasma DNA pool in a simultaneous manner. In this work, we report that in open chromatin regions, cfDNA molecules show characteristic fragmentation patterns reflected by sequencing coverage imbalance and differentially phased fragment end signals. The latter refers to differences in the read densities of sequences corresponding to the orientation of the upstream and downstream ends of cfDNA molecules in relation to the reference genome. Such cfDNA fragmentation patterns preferentially occur in tissue-specific open chromatin regions where the corresponding tissues contributed DNA into the plasma. Quantitative analyses of such signals allow measurement of the relative contributions of various tissues toward the plasma DNA pool. These findings were validated by plasma DNA sequencing data obtained from pregnant women, organ transplantation recipients, and cancer patients. Orientation-aware plasma DNA fragmentation analysis therefore has potential diagnostic applications in noninvasive prenatal testing, organ transplantation monitoring, and cancer liquid biopsy.